Tradisi Melengkan dalam Perkawinan Adat Masyarakat Gayo di Kecamatan Bandar Kabupaten Bener Meriah - Maya Apriana; Ikhwan (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2020)
this study focus on tradition of melengkan in marriage culture of Gayonese society. The main issues of this study are the background of melengkan, the process of melengkan ritual and the process of preservation melengkan tradition. The aims of study are to know detail of the background, ritual procession and preservation of melengkan tradition. This study uses qualitative approaches of observation, interview and documentation. Data are analyzed through inductive qualitative approach. The results show that melengkan is part of local wisdom in system marriage tradition of Gayonese. Melengkan is art of speech or poems by using specific Gayo language. The processions are in two phase (1) during proposing of marriage (2) the ritual of delivering bride and groom. This tradition is not being performed if the marriage took place in religious affair office, but melengkan still performed if the marriages are held in personal house or in meunasah, the preservation efforts are including the competition of melengkan, socialization in community and schools, especially in school by adding special subject in class for study basic of melengkan.